آليات الحفاظ على الاستقرار في ضوء السنة النبوية: معاملة الكبراء نموذجا ............................................... Mechanics of Stability in the light of Prophet’s Sunnah: Treatment of Leaders as Specimen - لعور ربيع (الدراسات الإسلامية, 2018)
People follow their leaders in rightness and wrongness and even if some people do not adhere to them, the majority will keep pursuing their way. The Messenger of Allah (peace and blessings of Allah be upon him) duly considered this principle in his call to the leaders of the three categories, namely the Muslims, the hypocrites and the disbelievers. For the first group, the Muslim leaders, he approved them for the leadership of their tribes and their guidance among their people profiting from their expertise and their place among their followers and has approved their views and judgments compatible with the law of Allah. As to the ones he has seen devoted to money have been maintained with group through it. As for the hypocrites’ leaders, he expressed a great reservation in their treatment and a great warning to ignore their mistakes and to guard against their conspiracies. He accepted their words being sure of their falsehood, abstained from killing them, eager to seek forgiveness for them. As for the category of the disbelievers’ leaders, he dealt with them very wisely; he continued to invite them to Islam, approving to keep their positions after their conversion. He also avoided killing them with the legitimacy of fighting them only in the case of actual interest. We find that the common denominator in dealing with all these groups is to maintain the stability of the nation and to consolidate the foundations of peace at home or abroad through avoiding the causes of trouble.